Weakness in the intensive care unit. Issue 5 (21st July 2022) - Walters, Jon
Abstract : When asked to assess patients in an intensive care unit (ICU) who have respiratory muscle weakness, oropharyngeal weakness and a vulnerable airway, our immediate thought may be of Guillain-Barré syndrome or myasthenia gravis, but there are many other possible causes. For example, previously unrecognised chronic neurological conditions may decompensate and require ICU admission. Clinicians can use various clinical clues to help recognise them and need to understand how patterns of weakness reflect differing causes of reduced consciousness on ICU. Additionally, patients admitted to ICU for any reason may develop weakness during their stay, the most likely cause being ICU-acquired weakness. Assessing patients in ICU is challenging, hampered by physical barriers (machines, tubes), medication barriers (sedatives) and cognitive barriers (delirium, difficulty communicating). Nonetheless, we need to reach a clinical diagnosis, organise appropriate tests and communicate clearly with both patients and ICU colleagues.